Effects of tea products on in vitro starch digestibility and eating quality of cooked rice using domestic cooking method. Issue 11 (23rd October 2020) - Fu, Tiantian; Niu, Liya; Li, Yun; Li, Dongming; Xiao, Jianhui
Abstract : Cooked rice (CR) is a staple diet for many people, but exhibits the high glycemic index that makes it difficult to control the blood glucose. Abstract : Cooked rice (CR) is a staple diet for many people, but exhibits the high glycemic index that makes it difficult to control the blood glucose. Herein, instant green tea (IGT), instant black tea (IBT) and matcha (Mat) (1, 2 and 3% w/w, rice basis) were added to lower the in vitro starch digestibility and improve the eating quality of CR prepared with an electric rice cooker. The results showed that adding tea products at each level could remarkably reduce the in vitro starch digestibility of CR. Compared with IGT and IBT, 3% of Mat significantly decreased the contents of rapidly digestible starch (RDS) from 72.96% to 60.99%, the digestion rate constant ( K ) from 11.4 × 10 −2 to 8.68 × 10 −2 min −1 and the expected glycemic index (eGI) from 77.55 to 66.86. Furthermore, the gas chromatography-ion migration spectrum was analysed to confirm that the tea products endowed the cooked rice with a refreshing flavor by inducing the redistribution of the main aroma components. Moreover, it was found that increasing the ordered crystal structure of rice grains played a major role on lowering the starch digestion, which was demonstrated by the results of the Rapid Visco Analyser, scanning electron microscopy, X-ray diffraction and Fourier transform infrared spectroscopy. These findings suggested that cooking rice with tea products, especially Mat, can be useful in enhancing the palatability and slowing the in vitro digestion properties of CR.